2006
DOI: 10.1039/b513786a
|View full text |Cite
|
Sign up to set email alerts
|

Regular arrays of microdisc electrodes: simulation quantifies the fraction of ‘dead’ electrodes

Abstract: Arrays of microdisc electrodes have found widespread use in electroanalysis. These are commonly produced lithographically and practical arrays may contain up to hundreds of individual disc electrodes (e.g. of gold, platinum, indium,...) to maximise sensitivity and minimise limits of detection. Typically, however, the lithographic fabrication process is imperfect resulting in a significant fraction (often tens of percent) of electrochemically inactive electrodes. We demonstrate that a 2-dimensional simulation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 12 publications
(21 reference statements)
2
50
0
3
Order By: Relevance
“…Therefore an easier approach is to use a simulation method, the details of which have been described elsewhere. [12][13][14] Comparison of experimental data with numerical simulations revealed that the actual number of discs on the array corresponds to 170 and 1550 electrodes for array 1 and array 2, respectively (see Table 1). …”
Section: Characterization Of the Ultra-microelectrode Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore an easier approach is to use a simulation method, the details of which have been described elsewhere. [12][13][14] Comparison of experimental data with numerical simulations revealed that the actual number of discs on the array corresponds to 170 and 1550 electrodes for array 1 and array 2, respectively (see Table 1). …”
Section: Characterization Of the Ultra-microelectrode Arraysmentioning
confidence: 99%
“…The only way to quantitatively determine the actual number of electrodes on the array is to either i) electrochemically plate copper metal on the array so that they can be physically counted or ii) fit several cyclic voltammograms for the ferrocyanide/ ferricyanide couple as a function of scan rate with that predicted via theory. 13 Given that the array in this example has over 2000 electrodes, option i) would be tedious and time consuming. Therefore an easier approach is to use a simulation method, the details of which have been described elsewhere.…”
Section: Characterization Of the Ultra-microelectrode Arraysmentioning
confidence: 99%
“…The fraction of the active electrodes is 20% which is less than the typical value of active electrodes in conventional microdisk electrodes arrays. 41,44 This is due to deficiencies in the final etching step of the fabrication process. Presumably, due to slight inhomogeneities in oxide layer thicknesses, the reactive ion etching has not been able to open all the microdisks and hence the low active number.…”
Section: Experimental Validationmentioning
confidence: 99%
“…Nanoelectrode arrays were fabricated over gold microband electrodes that had previously been made using standard photolithographic techniques as described previously in 12,13 . Chips containing gold microbands were spin-coated with a 100nm layer of PMMA 950K.…”
Section: Fabrication Of Disk Nanoelectrode Arraysmentioning
confidence: 99%